Improving Grade 5 Science Learning Outcomes Throught Educational Videos At SDN Tanjung Jati 2 - Nova Elisa Lestari; Annisa Aditya Ramadhani; Rinneke Anggraeni Muffidah Sari (Journal of Action Research in Education, 2023)
This research aims to improve the learning outcomes of 12 people at SDN Tanjung Jati 2. The research method used is qualitative and quantitative analysis techniques, which begins with a learning plan and continues with action in class as well as reflection on initial actions and planning after learning, research results There was an increase in students' understanding of the subject matter as shown by student learning outcomes from pre-cycle to cycle II. In the Pre-Cycle, the average student score was 49 with classical completeness of 42%. In Cycle I, the average student score was 93 with classical completeness of 100%. In cycle II, the average student score was 94 with classical completion reaching 100%.